Primary Myeloid Sarcoma of the Ileum and Mesentery Causing Small Bowel Obstruction: Case Report and Literature Review - Nikolovski, Andrej; Mladenovikj, Dragoslav; Veljanovska, Aleksandra; Petrusevka, Gordana (Lietuvos chirurgija, 2020)
Myeloid sarcoma (extramedullary myeloblastoma, granulocytic sarcoma, chloroma) is an extramedullary isolated malignant tumor of myeloblasts and immature myelocytes. It can occur anywhere in the body as a solitary tumor or can be accompanied with acute myeloid leukemia. We are presenting a case of a young male patient that presented with sings of a small bowel obstruction and a palpable tumor mass in the abdomen. After uneventful postoperative period, the immunohistochemistry analysis reported an extramedullary myeloid sarcoma since a normal bone marrow biopsy was revealed.
Keywords: primary myeloid sarcoma; small bowel obstruction